Teaching strategies based on multiple intelligences to develop reading skills in sophomore students at Abelardo Moncayo high school in Atuntaqui during 2021-2022 - Guerrero Reinoso, Milena Alexandra (2022)
Adapt teaching strategies based on multiple intelligences in the development of reading skills in sophomore students at Abelardo Moncayo high school in Atuntaqui during 2021 - 2022.